Parenting Styles of Single Parents and the Foundation of Social and Emotional Development in Early Childhood - I Wayan Karta; Aulia Dwi Amalina Wahab; Ni Luh Putu Nina Sriwarthini (Jurnal Pedagogi dan Pembelajaran, 2026)
The increasing number of single parent families highlights the need to understand how parenting within such family structures influences the development of early childhood social competence and emotional stability. This study aims to analyze and explore the impact of single parent caregiving on children’s social competence and emotional stability across different cultural contexts. A qualitative approach with a phenomenological design was employed to examine the influence of single parent parenting on early childhood social competence and emotional stability in various cultural backgrounds. The study involved 12 children aged 5-8 years raised in single parent families. Data were collected through participant observation, in-depth interviews, and focus group discussions using semi structured interview guides and observation protocols. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing and verification. The findings show that children in single parent families exhibit variations in social competence and emotional stability despite the application of democratic parenting, influenced by caregiver roles, family structure, experiences of loss, cultural norms, and social support. Extended family and social environment support can enhance children’s emotional security, whereas inconsistent parenting and trauma may hinder social emotional development. This study concludes that culturally responsive parenting interventions are needed to support early childhood social competence, emotional stability, and resilience. The implication is that parents, educators, and policymakers should strengthen social support and develop culture-based parenting programs for single-parent families.